Dampak Strategi Digital Marketing terhadap Kepercayaan Pelanggan Cafe Aola Paciran Lamongan - Indrika Dwi Febianti; Siti Musarofah; Mesra Surya Ariefin; Dadang Wiratama (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the impact of digital marketing strategies on customer trust at Cafe Aola Paciran Lamongan. The research employs a descriptive qualitative approach involving 16 informants selected through purposive sampling, specifically customers who are familiar with or have interacted with Cafe Aola through digital media. Data were collected through semi-structured interviews, questionnaires, and documentation, while data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The results show that Cafe Aola’s digital marketing strategy is dominated by the use of social media, particularly TikTok and Instagram. TikTok plays a significant role in expanding promotional reach through the For Your Page (FYP) algorithm, while Instagram supports visual branding and structured information delivery. High-quality digital content that is attractive, aesthetic, and informative has been proven to increase brand awareness and shape customer expectations. The level of customer trust in Cafe Aola is relatively high, as indicated by the consistency between digital information and actual experience, as well as the absence of misleading or exaggerated information. In addition, responsive, friendly, and communicative digital interactions further strengthen customer trust. Digital marketing strategies also have a positive impact on customer behavior, including increased intention to visit, willingness to revisit, and readiness to recommend the cafe to others. Thus, digital marketing functions not only as a promotional tool but also as a strategic means of building customer trust and long-term relationships.